The use of the quick response code in the teaching of the human anatomy of the locomotor apparatus - Dias, Nícolas Basana; Souza, Mariany Fernanda Escola de; Krueger, Eddy; Fornaziero, Célia Cristina; Fernandes, Eduardo Vignoto (Seven Editora, 2023)
The study of human anatomy is a relevant part of the curriculum of health course graduation students. Given the constant reduction of hours destinated to the study of Anatomy and the debates regarding new teaching methods, the use of the Quick Response Code (QR code) has shown to be promising. Therefore, the Anatomy Department at the State University of Londrina (UEL) has developed a cataloging process concerning anatomical structures with the application of QR code, and this paper has the purpose of reporting on such experience. In the process, the structures dissected in UEL’s Anatomy Laboratory were cataloged based on a spreadsheet which contained the correlation between these structures and numbers; the information regarding each structure was then transcribed into a QR code using a digital generator, with posterior printing, lamination and attachment to the body part. The labels were made by sewing the numbered tags onto the structures. Within the discussion regarding alternative teaching methods, examples can be given regarding lamination, three- dimension projection and prospection. The use of the QR code has proven to be a valid alternative in aggregating knowledge to academic curriculum. Through the activities performed in the process of cataloging, it was possible not only to dedicate more time to the theorical and practical learning of human anatomy, but also to increase the independence in studying and developing research. Furthermore, there is an opportunity to expand the analysis directed toward human anatomy teaching and toward new learning methods. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-117